Effect of bowel preparation before vaginal surgery on perioperative outcomes in patients with pelvic floor disorders - Y.Y. Liu; Y. Liang; X.D. Li; H. Deng; X. Yang; J.L. Wang (IMR Press, 2020)
Purpose: The aim of this study was to compare mechanical bowel preparation (MBP) with oral laxative against no bowel preparation on the perioperative outcomes for pelvic floor dysfunction (PFD). The need for bowel preparation before vaginal surgery was thus also investigated. Methods: PFD patients undergoing vaginal surgery in Peking University People's hospital from September 2017 to July 2018 were randomly assigned to MBP (n = 60) or control (n = 60) groups. The two groups were compared for the incidence of preoperative abdominal symptoms and overall patient satisfaction, intraoperative visualization of the surgical field assessed by the surgeon, and postoperative recovery outcomes. Results: There were no statistically significant differences between the two groups (p > 0.05) for surgical visualization, the surgeon's overall satisfaction, or for the rate of postoperative complications. However, patients in the MBP group reported more gastrointestinal symptoms and had reduced satisfaction compared to the control group (p < 0.05). Conclusion: The use of MBP before vaginal surgery reduces preoperative patient satisfaction while conferring no benefit in terms of optimizing surgical visualization and reducing postoperative complications. For patients with PFDs, it is safe and feasible to do without MBP before vaginal surgery.